First-in-man Experience of a New Transcatheter Edge-to-edge Repair System Neoblazar in Patients With Severe Tricuspid Regurgitation - Xiang Chen; Da Zhu; Maolong Su; Xu Chen; Pianpian Yan; Hongmei Wen; Bin Wang; Nianguo Dong; Xiangbin Pan; Yan Wang (Cardiology Discovery)
Objective:. Severe tricuspid regurgitation frequently leads to increased mortality and a poor prognosis. Transcatheter edge-to-edge repair (TEER) for tricuspid valve regurgitation has been reported as a safe alternative to traditional open-heart surgery. This study endeavors to assess the efficacy and safety of a newly designed Neoblazar TEER system in this high-risk population. Methods:. This investigation was structured as a prospective, single-arm, first-in-man trial in China (ClinicalTrials.gov number: NCT05497141). From August 2022 to October 2022, patients with severe tricuspid regurgitation were enrolled from 3 centers (Xiamen Cardiovascular Hospital, Fuwai Yunnan Cardiovascular Hospital, and Wuhan Union Hospital). The primary endpoint was achieving a minimum 1-grade reduction in tricuspid regurgitation at the 6-month post-TEER intervention, in addition to the pertinent New York Heart Association class. Scheduled echocardiographic evaluations were conducted at the following distinct intervals: baseline, discharge, 1 month, and 6 months post-TEER intervention. Results:. A total of 10 patients were enrolled in the study. Immediately after the TEER procedure with the Neoblazar system, massive tricuspid regurgitation (grade 5+) at baseline decreased to moderate-severe tricuspid regurgitation (grade 3+) in 2 patients and the optimal tricuspid regurgitation reduction (severe tricuspid regurgitation (grade 4+) to mild tricuspid regurgitation (grade 1+)) were achieved in 6 patients. After 6 months of follow-up, tricuspid regurgitation reduction was found to be durable in all enrolled patients, among whom at least 1 grade of tricuspid regurgitation reduction was sustained, even without reintervention. Consistently, the New York Heart Association class among these subjects significantly improved, with the percentage of patients categorized as class I–II increasing from 0/10 at baseline to 5/10 after 1 month (P = 0.015) and 8/10 after 6 months (P < 0.001). Conclusion:. Tricuspid TEER with the newly designed Neoblazar system appears to be a feasible and safe alternative in treating patients with severe tricuspid regurgitation. However, the implementation of larger and more robust randomized trials is still necessary for further verification of the potential benefits.